"Albanian Golgotha” – the exodus of Serbs to the Corfu island during World War I in the public discourse - Michalak, Paweł (Balcanica Posnaniensia. Acta et studia, 2017)
Both the Balkan Wars and World War I, and particularly the great migration of the Serbian army during the retreat to the Corfu island, which imprinted in the collective memory as the Albanian Golgotha, were among the most important reference points in the public discourse of interwar Yugoslavia. Official government circles tried to present them as the cornerstones for the building of a unified state of the Southern Slavs. The authorities supported all the initiatives which were commemorating those events. King Alexander Karađorđević was one of the most active in this field, he repeatedly personally graced the celebration of all events and battles or honoured their heroes. However, it should be noted that the Albanian Golgotha was such an important point of reference in the public discourse of interwar Yugoslavia not only because it became a kind of an instrument in the hands of politicians, especially the king, but also – and perhaps primarily – because it grew it roots in the broader social discourse, not only in politics but also in the media and culture – literature or the arts. It is also worth mentioning that the memory of these events was not a homogeneous one. For obvious reasons, it were the Serbs, who excelled in the worship of the Serbian soldiers, who sacrificed their blood for building a common Yugoslav state. While the attitude of Croats and Slovenes was not so clear. Therefore the cult of the Serbian army required an appropriate action from the state. One of the actions was a way of presenting these events in the daily press. The main aim of the author is to show how the cult of the sacrifice of the Serbian soldiers and civilians during World War I, and especially the mythologized Albanian Golgotha, was created and became one of the pillars on which authorities tried to build a Yugoslav identity and the prestige of the Karađorđević dynasty in the interwar period. A special attention is paid to the way of describing those events in the “Politika” daily, the most read and influential journal of interwar Yugoslavia.